If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(v + -5) = -7(v + 8) Reorder the terms: -7(-5 + v) = -7(v + 8) (-5 * -7 + v * -7) = -7(v + 8) (35 + -7v) = -7(v + 8) Reorder the terms: 35 + -7v = -7(8 + v) 35 + -7v = (8 * -7 + v * -7) 35 + -7v = (-56 + -7v) Add '7v' to each side of the equation. 35 + -7v + 7v = -56 + -7v + 7v Combine like terms: -7v + 7v = 0 35 + 0 = -56 + -7v + 7v 35 = -56 + -7v + 7v Combine like terms: -7v + 7v = 0 35 = -56 + 0 35 = -56 Solving 35 = -56 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 16=16H | | 2x^2-8x-80=0 | | 8t-18=38+t | | X+6+6x=41 | | -7(v-5)=-7 | | 100x^2-y^4= | | 20s+4=13c-10 | | 9(x+6)=-9(3+2x) | | 7m-15-10m=6 | | (3y+5)=(4y-10) | | 5x^2=2+3x | | 5w+6-w=2 | | 4x+6=2x^2 | | 5x^2+2=3x | | 0=9x^2-39x+24 | | 25+1.75x=10+3.25x | | 6=y^2+5y | | 125=.005s^2+1.1s | | 2p^2-13p-20= | | -x+6(6x+2)=-2+7(-4+11) | | 0.04(4-1)=0.03(-1+8)+0.04 | | h=40t-5t^2 | | 18x^2+23x-6=0 | | 17n=-4 | | -4(n+3)-6=-2(n-7) | | 4y^2+y-3=0 | | 7r^2+48r-7= | | -(x+11)=9 | | -3(-9+x)=24 | | 3(a+2)=2(a-7) | | 11(4x+11)=-2 | | -4(-3+x)=48 |